SISTEM OTOMATIS PENGENDALI NUTRISI TANAMAN HIDROPONIK BERBASIS ARDUINO MENGGUNAKAN SENSOR TDS - Fanani, Mochamad Rizal; Hariono, Tholib (Lembaga Penelitian Pengabdian Masyarakat Universitas KH. A. Wahab Hasbullah, 2021)
Hydroponics is a farming technique without using soil as a growing medium but by utilizing water that suppressed the nutritional needs of plants. In this case, regular monitoring is needed, so that all plants can be provided whit both water and nutrient level, with the creation of an automation system for providing nutrition for hydroponic plants, it will gratly help the work of farmers, the system is made using the waterfall method. Some of the tools used include Arduino Uno, TDS sensors, pumps, and also waterflow sensors. The TDS sensor will detect the level of nutrients in the water used to irrigate the plants. When the nutrient conditions are low, the nutrient pump will turn on and release water into the water container used to irrigate the plants, the waterflow sensor works to detect the water discharge released by the pimp. The result obtained in this study are the error rate in reading the accuracy of PPM levels by the TDS sensor reaching 2.43%, the pump automation status is on when the PPM is below 600, and turns off when PPM level are aboce 600, as well as the accuracy of the waterflow sensor in detecting discharge the water released by the pump has an average level of accuracy that inhibits perfect, this is also supported by the Arduino microcontroller as a controller to process input data from several existing sensors.